GESSO AGRÍCOLA E ADUBAÇÃO NITROGENADA NA CULTURA DO MILHO EM SISTEMA PLANTIO DIRETO - Zardo Filho, Renato (2011)
A considerably part of the high nitrogen (N) rates applied in corn is not absorbed due root growth restriction by subsoil acidity. Gypsum is able to improve conditions for root growth and lead to greater N uptake efficiency, increasing corn yield. Thus to evaluate the effect of gypsum and N on top dressing on soil chemical attributes, root growth , mineral nutrition and corn development under no-tillage system, two experiments were carried out on a dystrophic clayey Typic Hapludox at Middle-South of Paraná State, being one field and another in undisturbed soil columns. In the field experiment, four rates of gypsum (0, 5, 10 and 15 t ha-1) and three rates of N-NH4NO3 (60, 120 and 180 kg ha-1) were set up into 4 × 3 factorial design with three replications. On soil columns, two gypsum rates (0 and 10 t ha-1) and two rates of N-NH4NO3 (0 and 180 kg ha-1) were used in a 2 × 2 factorial design with five replicates. In both experiments, gypsum was applied on the surface, one week before sowing and 45 kg N ha-1 was applied at sowing. Were analyzed the changes in chemical soil properties, root development, nutrient uptake by corn in both experiments. On the field experiment were quantified the yield and efficiency in N use, and on the columns experiment the amount of N-NO3 - leaching was determined 45 days after the application of gypsum when the plants were cut off. On field experiment, gypsum increased levels of Ca2+, S-SO4 2- and P also decreased the exchangeable Al3+ level on subsoil layers. N rates raised up N-NO3 - levels throughout the soil profile and Ca2+ in 0,4-0,6 m. The increase in Ca2+ and S-SO4 2 levels on soil profile, as well the decrease on Al3+ saturation by gypsum application, improved plant root growth, and increased N, P, K, Ca, S, Zn and Mn extraction by maize, leading in increased corn grain yield. On top of that, gypsum rates improved N use efficiency by corn. In the soil columns experiment, gypsum and N application improved the plants roots to higher depths, which results in better plants dry matter and greater N, P, K, Ca, Mg, and S extraction. The amount of N-NO3 - leached on soil columns was higher when N was applied without gypsum. Gypsum application increased N uptake by plants due the root system increase and also increased of S-SO4 2-supply in soil, thus reducing the amount of N-NO3 - in the soil and leached. This results showed that gypsum use reduce losses of N-NO3 - leached by increasing N plants uptake, having as a result better N use efficiency contributing to higher corn yield sustainability.